Subchronic Hepatotoxicity Evaluation of 2,3,4,6-Tetrachlorophenol in Sprague Dawley Rats - Darol E. Dodd; Linda J. Pluta; Mark A. Sochaski; Deborah A. Banas; Russell S. Thomas (Journal of Toxicology)
Male Sprague Dawley rats were exposed to 2,3,4,6-tetrachlorophenol (TCP) for 5 days, 2 weeks, 4 weeks, or 13 weeks. TCP was administered by gavage at doses of 0, 10, 25, 50, 100, or 200 mg/kg/day. Endpoints evaluated included clinical observations, body weights, liver weights, serum chemistry, blood TCP, gross pathology, and liver histopathology. There were no TCP exposure-related clinical signs of toxicity. Mean body weight decreased 12–22% compared to control in the 100 and 200 mg/kg/day groups. Serum ALT concentrations were increased in rats of the 200 mg/k/day. Liver weight increases were both dose- and exposure time-related and statistically significant at ≥25 mg/kg/day. Incidence and severity of centrilobular hepatocytic vacuolation, hepatocyte hypertrophy, and single cell hepatocytic necrosis were related to dose and exposure time. Following 13 weeks of exposure, bile duct hyperplasia and centrilobular and/or periportal fibrosis were observed in rats primarily of the highest TCP dose group. Blood TCP concentrations increased with dose and at 13 weeks ranged from 1.3 to 8.5 μg/mL (10 to 200 mg/kg/day). A NOAEL of 10 mg/kg/day was selected based on the statistically significant incidence of hepatocyte hypertrophy at doses ≥25 mg/kg/day.